Antifungal Effects of Staining Process on Wood: Hardness, Gloss, and Color Change - Mehmet Budakçı; Mustafa Korkmaz; İpek Karal (BioResources, 2022)
This study determined the effects of wood staining on wood-destroying fungi. To achieve this goal, different types of wood samples were used, including Scotch pine (Pinus sylvestris L.), Eastern beech (Fagus orientalis Lipsky), sessile oak (Quercus petraea Liebl.), and mahogany (Entandrophragma cylindricum). Aniline (C6H2NH2), chemical (tannin (C14H10O9) + potassium dichromate (K2Cr2O7)), and Van Dyke brown stains (Fe2O3MnO2 + K2Cr2O7 + H2O) were applied to the samples, because a walnut color (brown) is preferred by customers. The stained samples were exposed to Fomitopsis palustris and Coriolus versicolor, and mycelium growing on wood was observed for 3 months. Hardness, gloss, and total color change tests were applied to the samples to determine the antifungal effects. The results showed that staining increased the total color change values of the wood, while decreasing in the gloss and hardness values. The chemical stain showed antifungal effects against both fungi.